PENGARUH PENGELOLAAN KEARSIPAN MODERN TERHADAP EFISIENSI KERJA PEGAWAI: Studi Kasus di Kantor Dinas Kehutanan Provinsi Lampung - Artane, Komang; Rosidah, Rosidah; Herowandi, Muhammad (Jurnal Progress Administrasi Publik, 2025)
This research is descriptive quantitative research. This research aims to determine the effect of modern archives management on the work efficiency of employees at the Lampung Province Forestry Service Office. This research uses primary data which collects data using a questionnaire. In this research, researchers used quantitative analysis, simple linear regression analysis and analysis of the coefficient of determination with the help of SPSS 26.0. The population in this study was all employees of the Lampung Province Forestry Service Office, totaling 70. The results of the research obtained using the t test showed that modern archives management had a positive and significant effect on employee work efficiency values, with the results of hypothesis testing where tcount (8,176) > ttable (1,995). In the coefficient of determination test, the data obtained was 49,6% which could be explained by modern archives management, while the remaining 50,4% could be explained by the influence of other variables not examined by the author.   Keywords: Archives; Efficiency; Employee; Management